2011
DOI: 10.1007/s00520-011-1156-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired physiological function and health-related QOL in patients before hematopoietic stem-cell transplantation

Abstract: Health-related QOL and loss of physiological function have a variety confounding factors. Patients scheduled for HSCT may have physiological weaknesses prior to transplant, which need to be considered when planning an exercise regimen during and after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 42 publications
5
44
1
Order By: Relevance
“…12,13 Functional capacity impairments in patients with chronic GVHD have also been shown to mediate adverse changes in post-HCT functional performance associated with symptom burden. 31 There are limited data regarding 6MW in HCT, 32 and no data that we are aware of that explore the feasibility or prognostic value of cardiopulmonary testing in patients planning to undergo HCT. Muffly et al 33 recently reported on the use of a comprehensive geriatric assessment before allogeneic transplant, which incorporated a 'Frailty Index' that included walk speed and grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Functional capacity impairments in patients with chronic GVHD have also been shown to mediate adverse changes in post-HCT functional performance associated with symptom burden. 31 There are limited data regarding 6MW in HCT, 32 and no data that we are aware of that explore the feasibility or prognostic value of cardiopulmonary testing in patients planning to undergo HCT. Muffly et al 33 recently reported on the use of a comprehensive geriatric assessment before allogeneic transplant, which incorporated a 'Frailty Index' that included walk speed and grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…1 Before allo-HCT, patients' physical performance is already affected due to the disease itself and prior treatment. 2,3 Physical inactivity, resulting from long hospitalization and side effects or complications, leads to an additional loss of physical performance. A recent review shows that patients after HCT are likely to have long-term difficulties with physical functioning, fatigue, distress and psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Given its intensity and potential short and long term complications, there are significant risks of physical and psychological morbidity following treatment [1]. Several studies have identified that the side effects of an alloBMT can be long term and include physical impairments such as muscle weakness and reduced endurance; persistent symptoms such as fatigue; and poor health-related quality of life (HRQoL) [2,3]. Whilst the side effects observed in allogeneic and autologous BMT are similar, those experienced following an alloBMT are more numerous and severe due to prolonged hospital length of stay and greater risk of debilitating long-term complications such as graftversus-host-disease [1,4].…”
Section: Letter To Editormentioning
confidence: 99%
“…Firstly, patients present to BMT with reduced muscle strength, exercise capacity and HRQoL when compared to the healthy population [3]. The ability therefore to maximise their health status before the insult of treatment is preferred.…”
Section: Letter To Editormentioning
confidence: 99%